2018
DOI: 10.3390/su10020549
|View full text |Cite
|
Sign up to set email alerts
|

The Selected Method and Tools for Performance Measurement in the Green Supply Chain—Survey Analysis in Poland

Abstract: The methods and tools for the performance measurement and evaluation of the green supply chain management are very important elements for the construction and function of this type of supply chain. The result is a presentation of the considerations underlying a very general model, which presents some selected tools, but no breakdown of individual industries. The considerations undertaken are important and have scientific added value as usually in practice, a very large number of tools are used to assess the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 95 publications
(108 reference statements)
0
37
0
Order By: Relevance
“…Based on the content review of the literature, we found that the SSCM implementation practices typically extend existing SCM practices into the realm of sustainability [30]. Markman and Krause [33] argue that sustainable practices should satisfy two inseparable criteria: (1) they must enhance ecological health, meet ethical standards to enhance social justice, and improve economic vitality; and (2) they must prioritize the environment first, society second, and economics third.…”
Section: The Categories and Practices Of Sscm Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the content review of the literature, we found that the SSCM implementation practices typically extend existing SCM practices into the realm of sustainability [30]. Markman and Krause [33] argue that sustainable practices should satisfy two inseparable criteria: (1) they must enhance ecological health, meet ethical standards to enhance social justice, and improve economic vitality; and (2) they must prioritize the environment first, society second, and economics third.…”
Section: The Categories and Practices Of Sscm Implementationmentioning
confidence: 99%
“…The selection of cases was based on the Airiti Library online database, the most comprehensive collections of scholarly Journals in the Chinese research community, which was available to help conduct our targeted literature search (most selected papers were written in Chinese with English abstracts and some papers were written in English). From the historical development perspective, the sustainable considerations of the supply chain first evolved into the green supply chain in early 2000, and then become more widely labeled as SSCM in mid-2000 [30]. Next, using the keywords of "Sustainable Supply Chain" and "Green Supply Chain" between the years 2000 and 2018, it yielded 180 papers including journal papers, conference papers, and unpublished theses.…”
mentioning
confidence: 99%
“…However, the measurements selected and used in the evaluation are very much in line with those put forward in present literature (see e.g., [7,14,36,40]). However, the municipality's call for additional measurements targeting more local aspects regarding the transport situation, work environment as well as the positive results of increased information quality due to improved order and structure, do point at the need for also including more qualitative aspects to the equation, in line with Tundys and Wiśniewski [30] stating that sustainable performance measurement in supply chain should include qualitative indicators. Besides this, by considering energy usage, the efficiency of the system was targeted, adding the economic dimension to variables furthermost aiming to capture the environmental and social consequences of the initiative.…”
Section: Discussionmentioning
confidence: 94%
“…Performance measurements and the use of indicators are useful for decision making, estimating progress and improvements as well as enabling comparisons and benchmarking [28], and are of importance to monitor the sustainability of transport [29]. Furthermore, measurement and evaluation can provide justification for the implementation of green supply chain initiatives [30].…”
Section: Performance Measurement In a City Logistics Contextmentioning
confidence: 99%
See 1 more Smart Citation